Ziarah Ke (Pemikiran) Hatta: Dari Koperasi Menuju Ke Ekonomika Etik - Hudiyanto, - (Unisia, 2016)
Mohammad Hatta is one of Indonesian independence proclamator. Beside as a proclamator, Hatta denoted an Indonesian economics scholar who tried to understand the history and the problem of economical problem ofhis nation. He, then, formulated comprehensively the economic system of Indonesia that written at article 33 of Indonesian Constitution 1945. The following article, the author traces the implication of Hatta's thought regarding Cooperation in term of the developing of economics ethics of Indonesia